The role of growth hormone in assisted reproduction - Quaas, Alexander M.; Penzias, Alan S.; Adashi, Eli Y. (Frontiers in Endocrinology, 2022)
In contemporary ART, the use of “add-ons” during ovarian stimulation has increased, especially in poor responders. Growth Hormone (GH) is an adjunctive therapy that has been studied extensively in the translational and clinical setting, with an ongoing scientific debate over its effectiveness and optimal use. In this review, we aim to provide an overview of the physiologic basis for the use of GH in ART, and to summarize the latest evidence regarding its clinical use, primarily as an adjunct to ovarian stimulation, but also in the IVF lab and with regards to its effects on the endometrium.